2010
DOI: 10.1007/s10548-010-0156-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalographic and Magnetic Resonance Spectroscopy Evidence of Regional Functional Abnormality in Mesial Temporal Lobe Epilepsy

Abstract: Mesial temporal lobe epilepsy (mTLE) with mesial temporal sclerosis (MTS) is a recognized epilepsy syndrome which is successfully treated with mesial temporal lobe resection. However, recent studies suggest that mTLE is more than a "focal" disease process. The objective of our study was to determine the presence and extent of functional abnormalities outside of a defined structural abnormality in epilepsy patients with mTLE. We used a prospective age-matched controlled design to study eight consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Our results were based on data collected from a small set of 10 patients. Based on our experience we believe that 1 H MRS could be a useful paraclinic method not only in patients with refractory epilepsy, but also in patients suffering from solitary or sporadic epileptic seizures generated in the temporal lobe (Chernov et al 2009;Shih et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were based on data collected from a small set of 10 patients. Based on our experience we believe that 1 H MRS could be a useful paraclinic method not only in patients with refractory epilepsy, but also in patients suffering from solitary or sporadic epileptic seizures generated in the temporal lobe (Chernov et al 2009;Shih et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common diagnoses where the 1 H MRS is applied is epilepsy (Starčuk et al 2005;Fojtíková et al 2007;Shih et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the histological examination of the temporal lobe white matter in their series showed no abnormalities. 17 Similarly, Shih et al 23 reported their results from a series of 8 patients with MTS who underwent proton MRS of the lateral temporal lobe. These authors found that the NAA concentration was lower in the lateral temporal lobe on the same side as the MTS in 50% of their cases, while the concentration of Cho was increased in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical investigators have demonstrated with the aid of proton MRS that in cases of MTS, the ipsilateral extrahippocampal temporal lobe may have altered metabolism. 6,[17][18][19]23,24,26 Meiners et al 17 reported their experience with a series of 11 patients with hippocampal sclerosis who underwent single-voxel extrahippocampal temporal lobe proton MRS (Table 3). They found that the white matter of the temporal lobe ipsilateral to the hippocampal sclerosis demonstrated decreased concentrations of NAA, marked increase in Cho concentrations, a slight increase in Cr concentrations, and decreased NAA/Cho and NAA/Cr ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation